Features of Metabolic Associated Fatty Liver Disease in the Central Asian Population in Low and High Altitudes - Toktogulova, Nurgul; Breidert, Matthias; Sultanalieva, Roza; Tuhvatshin, Rustam; Kazieva, Altynai (Gaceta Médica de Caracas, 2022)
Today, there is insufficient knowledge about the course of metabolically associated fatty liver disease (MAFLD) in Asian populations living at different altitudes. Our article presents the results of the study of MAFLD in individuals with different body weights in conditions of high-mountain hypoxia. To study the course of MAFLD in lean and obese patients living in the conditions of low and high mountains of Kyrgyzstan. An open comparative study of Asian patients with MAFLD with and without type 2 diabetes mellitus (DM2) living in low and high mountains was performed. In each category of patients, the lean (BMI≤23) and obese (BMI> 23) groups were considered. The anthropometric parameters and biochemical parameters of blood were determined. The liver fibrosis index was calculated using the FIB Score. It was found that residents of the high mountains with MAFLD had a lower BMI compared to the lowlanders. Low blood glucose and HbA1c levels are observed in patients with high BMI living in high altitude areas compared with lowlanders, especially in combination with DM2. In the group of obese patients with MAFLD living in highlands, low total cholesterol, low-density lipoproteins and glomerular filtration rate are observed. A high risk of fibrosis was noted in the group of lean patients in both regions. Our results indicate that the study of the effect of chronic high-altitude hypoxia on the course of MAFLD requires prospective population-based studies.